One Health platforms and regulations in Southeast Asia - Thao Thi Bich Nguyen; Sinh Dang-Xuan; Lam, Steven; Hung Nguyen-Viet; Unger, Fred (International Livestock Research Institute, 2024)
The findings presented here offer a comprehensive overview of regional efforts in Southeast Asia, highlighting progress and opportunities to enhance the One Health approach to address the region’s health and environmental challenges.